Constitutive model for the dynamic response of a NiTi shape memory alloy - Shi, Xiaohong; Zeng, Xiangguo; Chen, Huayan (Materials Research Express, 2016)
In this paper, based on irreversible thermodynamic theory, the Helmholtz free energy function, was selected to deduce both the master equations and evolution equations of the constitutive model of a NiTi alloy under high strain. The Helmholtz free energy function contains the parameters of the reflecting phase transition and plastic property. The constitutive model for a NiTi alloy was implemented using a semi-implicit stress integration algorithm. Four successive stages can be differentiated and simulated: parent phase elasticity, martensitic phase transition, martensitic elasticity, and dislocation yield. The simulation results are in good agreement with the experimental results.